DISIPLIN KERJA (STUDI KASUS GURU SMK NEGERI DI KECAMATAN CIKARANG BARAT) - Sarjana, Sri (Humanus, 2013)
The objective of this research is to know the relationship between supervision and punishment with work discipline of vocational high school teacher. The research is conducted on state vocational high school subdistrict of West Cikarang, Bekasi District. The research method used survey method with the correlation approach to data collection tool using questionnaires. The respondents were  state vocational high school teachers who are in the subdistrict of West Cikarang, Bekasi district as many as 80 teacher selected by two stage random sampling technique. Instrument calibrated by using validity and reliability test. The data processing is used regression analyze technique and simple correlations with multiple regression and correlations. The result of the research show : First, there is positive correlation between supervision (X1)  with work discipline (Y) with correlation coefficient ry1 = 0,452 and similarity regression Ŷ = 42,327 + 0,609 X1. Second, there is positive correlations between punishment (X2) with work discipline (Y) with correlation coefficient ry2 = 0.658 and similarity regression Ŷ  =  27,406 + 0,748X2. Third, there is positive correlation between supervison (X1) and punishment (X2) with work discipline (Y) with correlation coefficient ry12 = 0,449 and similarity regression Ŷ = 0,024 + 0,413X1 + 0,648X2. Based on the result can conclude that work discipline could be increase to strengthen supervision and punishment. Kata kunci : discipline, supervision, punishment